THE IMPORTANCE OF INTERDISCIPLINARY WORK SHOWS IN MUNICIPAL ELEMENTARY SCHOOL SANTA ROSA, FORMIGUEIRO, RIO GRANDE DO SUL - Corrêa, Luiz Liberato Costa; Fraga, Jussara Pires de; Moreira, Saionara; Peixoto, Daniela Concari; Grigoletto, Daniele (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This paper aims to disseminate relevant information on the first show of interdisciplinary work involving teachers in partnership arts, science, literature and pedagogy together with students in Municipal Elementary School Santa Rosa in municipality of Formigueiro, Rio Grande do Sul. Thus contributing to the development and school knowledge, combined with scientific research, culture and interaction between school, students and local community.